Novel welding distortion analysis method for large welded structures using orthotropic thermal expansion coefficients. Issue 4 (7th July 2021) - Seo, Hyun-Duk; Lee, Jae Min
Abstract: This paper proposes an effective numerical method to predict welding distortion for large welded structures. To predict welding distortions, inherent strain-based methods are computationally efficient and widely used in engineering fields. However, there are some drawbacks such as the generation of undesirable longitudinal forces and the use of vector-type input variables. Equivalent loads are derived through finite element formulation considering orthotropic thermal expansion conditions. Unlike previous methods, the proposed method predicts transverse shrinkage and angular distortion accurately, removing the undesirable longitudinal forces. In addition, scalar-type input variables are employed, which results in a convenient design procedure. The performance of the proposed method is verified through various examples including complex and large welded structures. Graphical Abstract: